2017
DOI: 10.1016/j.neuroimage.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness is differentially associated with cortical thickness in young and older adults

Abstract: Aging is associated with reductions in gray matter volume and cortical thickness. One factor that may play a role in mitigating age-associated brain decline is cardiorespiratory fitness (CRF). Although previous work has identified a positive association between CRF and gray matter volume, the relationship between CRF and cortical thickness, which serves as a more sensitive indicator of gray matter integrity, has yet to be assessed in healthy young and older adults. To address this gap in the literature, 32 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 62 publications
3
60
2
5
Order By: Relevance
“…That is, among this sample of OA, we have previously reported positive associations between CRF and white matter microstructure (Hayes, Salat, et al, 2015) and cortical thickness (Williams et al, 2016). Moreover, these studies have shown that HFOA exhibit structural metrics more similar to YA than the LFOA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…That is, among this sample of OA, we have previously reported positive associations between CRF and white matter microstructure (Hayes, Salat, et al, 2015) and cortical thickness (Williams et al, 2016). Moreover, these studies have shown that HFOA exhibit structural metrics more similar to YA than the LFOA.…”
Section: Discussionmentioning
confidence: 57%
“…Neuropsychological and face-name memory retrieval accuracy (Hayes, Alosco, et al, 2015; Hayes et al, 2016), diffusion tensor imaging data (Hayes, Salat, et al, 2015), and cortical thickness data (Williams et al, 2016) from this sample are reported elsewhere, with minor differences in the number of subjects in the analysis sample dependent on the integrity of the particular data points of interest (e.g., a subject may have completed the DTI scan, but not the fMRI scan). All participants gave written informed consent and received financial compensation.…”
Section: Methodsmentioning
confidence: 99%
“…The third model examined the association between the interaction of obesity PRS and MetS factor scores on cortical thickness, controlling for the main effects of latent MetS and obesity PRS as well as age, sex, population substructure, and PTSD factor scores. In all of these analyses, the vertex-wise significance threshold was set at p < .05, following recent research (Williams et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Research in noneating disorder populations has shown that some of these behaviors can significantly affect brain structure and function (Boraxbekk et al, 2015;Freund et al, 2012;Hadjikhani et al, 2015;Stice, Burger, & Yokum, 2013). Although exercise has the potential to increase brain volumes in old age, the opposite may be the case in young adults, and the amount of exercise also plays an important role (Williams et al, 2017;Wobrock, Hasan, & Falkai, 2012). For example, extreme exercise in ultramarathon runners was associated with reductions in temporal, occipito-parietal and anterior cingulate gray matter volumes, as well as reduced brain volume in the caudate nucleus (Freund et al, 2014); these alterations normalized on follow-up after 8 months.…”
Section: E F Fe Cts Of Exe Rc I Se H Yd Ra T Ion S T At U S Bi Nmentioning
confidence: 99%